1999
DOI: 10.1097/00007890-199907270-00018
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double-Blind, Multicenter Plasma Concentration Controlled Study of the Safety and Efficacy of Oral Mycophenolate Mofetil for the Prevention of Acute Rejection After Kidney Transplantation1

Abstract: MPA Cpredose and MPA AUC are significantly related to the incidence of biopsy-proven rejection after kidney transplantation, whereas MMF dose is significantly related to the occurrence of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
336
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(357 citation statements)
references
References 8 publications
17
336
2
2
Order By: Relevance
“…6 The MPA AUC estimates in patients with chronic GVHD 6 were also higher than in patients who received MMF early after HCT to prevent acute GVHD 30 but closely similar to MPA AUC estimates in patients who received MMF to prevent rejection after kidney transplantation. 29 Although trough levels of MPA correlate poorly with the MPA AUC, 30,35 total MPA trough concentrations of 1 to 4 g/mL have been provisionally considered within the therapeutic range in kidney transplantation recipients. 22,36,37 Total MPA trough concentrations among patients taking MMF at 1 g orally twice daily in the current study approximated this therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The MPA AUC estimates in patients with chronic GVHD 6 were also higher than in patients who received MMF early after HCT to prevent acute GVHD 30 but closely similar to MPA AUC estimates in patients who received MMF to prevent rejection after kidney transplantation. 29 Although trough levels of MPA correlate poorly with the MPA AUC, 30,35 total MPA trough concentrations of 1 to 4 g/mL have been provisionally considered within the therapeutic range in kidney transplantation recipients. 22,36,37 Total MPA trough concentrations among patients taking MMF at 1 g orally twice daily in the current study approximated this therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
“…Testing was done at 3 months after enrollment because the MPA AUC increases during the first 3 months after beginning treatment with MMF. [27][28][29] Total MPA and free MPA (ie, not bound to protein) concentrations were measured in the laboratory of Dr Pamala Jacobson at the University of Minnesota, using methods described previously. 30 Free MPA has biologic activity, whereas protein-bound MPA does not.…”
Section: Plasma Trough Concentrations Of Mpamentioning
confidence: 99%
“…There are large interindividual and intraindividual variations in MPA pharmacokinetic parameters [64]. As with CsA, there is mounting evidence that systemic exposure to MPA, as measured by the AUC, is correlated to clinical events [78]. However, trough MPA levels seem poorly correlated to the 12-h AUC of MPA, so that therapeutic drug-monitoring strategies for MMF will also have to be refined in the near future [64].…”
Section: Maintenance Therapymentioning
confidence: 99%
“…A randomized MMF concentration-controlled trial (RCCT) showed a significant correlation between prevention of graft rejection and MPA plasma trough levels and MPA-area under the concentration-time curve (AUC 0ª24 h ) (10). A prospective study in renal transplant patients has been designed to maintain MPA trough and AUC 0ª24 h concentrations within a target range (11).…”
Section: Barten Et Almentioning
confidence: 99%